PENGARUH DISIPLIN TERHADAP KINERJA KARYAWAN - Zakiyudin, Ais (www.bsi.ac.id, 2016)
Companies are required to be able to survive and win the competition .Therefore , the competitiveness , performance and good quality from all sources owned by the company , particularly the human resources ( HR ) quality . Humans are creatures of God's most perfect in the world . Humans have the power of thought , analysis and creativity to plan , organize , actualize , and controls everything according to function in management. The company has a challenge in order to move and control the employees to want to work in accordance with the company's expectations . This work is not something very easy to do . Due to the fact that many companies have difficulty in building human resources to move in accordance with the wishes of the company . This is because humans are creatures who have preferences , desires , have feelings , ideals and expectations that differ between human beings with each other . Discipline is basically reflects the extent of responsibility that one has to carry out tasks assigned to him . Labor discipline is defined , among others, if the employee always come and go home on time , doing all the job well and on time, carrying out orders from superiors, and comply with all company rules and norms apply. Employees as a major resource companies are required to provide optimal performance for the company . Human resources has a major role to the company's success in achieving its objectives. Keywords: Discipline, Employee, Performance